Analisis Spasial Kejadian DBD di Wilayah Kerja Puskesmas Oesapa Tahun 2019 - Ximenes, Yohanes A. W.; Manurung, Imelda F. E.; Riwu, Yuliana R. (Timorese Journal of Public Health, 2019)
Oesapa Health Center is a health center that has the highest number of dengue cases in Kupang City in 2019 and spread throughout the Puskesmas working area. Regional-based disease management analysis techniques using spatial analysis can be used to facilitate the determination of the DHF problem solving intervention program. Spatial analysis is used to determine the pattern of disease spread and potential areas of dengue transmission based on area. The purpose of this study was to determine the pattern of dengue delivery, the spread of dengue incidence based on population density, the House Index and Container Index and the buffer. This type of research is a descriptive survey with a case study design. The sampling technique used total sampling with 98 people. The results of spatial analysis using Quantum GIS show the distribution pattern of dengue incidence with Clustered pattern with NNI value of 0,60 <1, the entire work area of Oesapa Health Center is included in the category of high population density, House Index and Container Index with the highest incidence of DHF in Oesapa and Lasiana Subdistrict and buffer analysis shows the tendency of dengue disease transmission in most cases to occur within a 100 meter radius, so the Oesapa Community Health Center work area is a high risk area for dengue transmission. Mosquito Nest Eradication Activities can be carried out by the community to prevent the spread of dengue disease.